1996
DOI: 10.1016/0550-3213(96)00309-4
|View full text |Cite
|
Sign up to set email alerts
|

Gauge theories of Josephson junction arrays

Abstract: We show that the zero-temperature physics of planar Josephson junction arrays in the self-dual approximation is governed by an Abelian gauge theory with periodic mixed ChernSimons term describing the charge-vortex coupling. The periodicity requires the existence of (Euclidean) topological excitations which determine the quantum phase structure of the model. The electric-magnetic duality leads to a quantum phase transition between a superconductor and a superinsulator at the self-dual point. We also discuss in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
237
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(241 citation statements)
references
References 54 publications
4
237
0
Order By: Relevance
“…We are led to predict the above startling properties for bosonic Quantum Hall systems, such as someday might be obtained from superconductor-insulator transitions in thin films, or from Josephson-junction arrays [50][51][52][53][54]. Unfortunately, these predictions cannot yet be tested with ordinary superconductors, because charge carrier densities and mobilities in these systems do not put them into the quantum Hall regime [55].…”
Section: Universal Critical Points Are Predicted For the Flowmentioning
confidence: 99%
“…We are led to predict the above startling properties for bosonic Quantum Hall systems, such as someday might be obtained from superconductor-insulator transitions in thin films, or from Josephson-junction arrays [50][51][52][53][54]. Unfortunately, these predictions cannot yet be tested with ordinary superconductors, because charge carrier densities and mobilities in these systems do not put them into the quantum Hall regime [55].…”
Section: Universal Critical Points Are Predicted For the Flowmentioning
confidence: 99%
“…It is interesting to notice that in (3.2) what lead to confinement is the condensation of the topological defects that enter the theory as a minimally coupled current and, as we explained before, are associated on the lattice with the breaking the global gauge symmetry down to Z t . A similar phase was found in [18], in the context of effective field theories for 3-dimensional Josephson junction arrays, studying a model in which the original gauge group was non-compact and only the BF coupling was periodic. Also in (3.6), as expected, the further condensation of thet µ gives a volume law for the expectation value of the Wilson "surface".…”
Section: Condensation Of Topological Defects In the 4-dimensional Casementioning
confidence: 87%
“…In this magnetic condensation phase, a lenghty calculation shows that the self energy of a circular charge loop of radius R is proportional to R ln R, and this gives rise to logarithmic confinement of electric strings (logarithmic confinement phase) [18]. The monopoles Q are always in a plasma phase : their condensation (after the condensation of t µ ), as it was shown in [10], gives a volume law and thus the usual confinement strings.…”
Section: Condensation Of Topological Defects In the 4-dimensional Casementioning
confidence: 99%
“…Something very interesting happens when the additional marginal terms in the effective action combine with the original ones to give (7). Suppose, moreover, that the charge current is identified with the boundaries of the now open world-surfaces of the vortices as J µ = 2∂ ν Φ µν , so that the interaction can be combined into…”
mentioning
confidence: 99%
“…Mixed Chern-Simons fluids as representations of condensed matter systems where first introduced in [7], where it was shown that they capture all the essential physics of 2D Josephson junction arrays. In the same paper it was also pointed out that this two-fluid construction can be generalized to 3D, the topological interaction being encoded in what is known as the BF term [8].…”
mentioning
confidence: 99%